ประสิทธิผลเปรียบเทียบของแอนโดรเจนชนิดต่างๆที่มีต่อหน้าที่การทำงานของสมอง และต่อมใต้สมองส่วนหน้าในหนูตัวเมียแรกเกิด - อำพา เหลืองภิรมย์ (จุฬาลงกรณ์มหาวิทยาลัย, 1973)
The purpose of this study was to compare effective ness of various androgens on differentiation of brain function controlling adenohypophyseal regulating ovulation and nestrous cycle in neonatal rats. Five to one thousand micrograms of testosterone propionate (TP), 50-2500 micrograms androstenedione and 1000-2000 micrograms 5 ∝ - androstan-3 ∝ 0.1-17 one were administered subcutaneously into female infant rats of 3-12 days old in order to compare effects of these androgens on the day of vagina opening, pattern of vaginal smear as well as the incidence of sterility (I.S.) when the age of treated animals reaching maturity (up to 90 days old). Result showed that the critical percid of 1000 ug TP on altering the female type of brain differentiation was between 6-10 days old induced prompt persistent vaginal cornification right after the opening of the vagina while injection of TP after 10 days old were unable to influence the regularity of reproduction of the females treated at least up to 90 days of age. Treatment with androstenedione 500 and 2500 ug at 3 days of age showed 20 and 50% of the I.S. at 90 days old white dehydroepiandrosterone 1000 and 1500 ug showed 83.3 and 100% and TP as small as 5 ug and 10 ug showed 83.3 and 90% respectively. Surprisingly, high dose of TP (500-1000 ug) showed significantly delay or in some cases inhibiting effects on the canalization of the vaginal lumen inspite of the histological picture of the ovaries of these animals are very similar to animals who showed persistent vaginal cornification. The tranqulizing drug, reserpine, when given half a day prior to TP treatment (on day 4½ - 5 after birth), showed significant reduction of the incidence of sterility. Treatment with reserpine 7.5 and 10.0 ug prior to TP at 5 days of age showed 33.3 and 40% of the I.S. at 90 days old respectively. On the other hand, monoamine oxidase inhibitors, marplan and marsilid, when given one hour prior to reserpine and TP at the dose of 100 and 200 ug showed significant increased of the I.S. to 60 and 37.3% at 90 days old respectively. It is concluded that 1) Testosterone, but not other androgens, would be a specific hormone for determining brain sexual differentiation of neonatal rats 2) Metabolism of biologically active monoamines during critical period (6-10 days old) may probably play significant influences upon brain sexual differentiation. 3) Evidences favor the possibility of testosterone effect on brain sexual differentiation during the critical period of neonatal life via the metabolism of brain biogenic monoamines.